Gender Roles and Cultural Expectations: A Comparative Study of Mulan and Indonesian Society - Yuliasari, Ria; Virtianti, Rika; Sari, Ferdias Prihatna (Pujangga : Jurnal Bahasa dan Sastra, 2024)
Analysing films involves more than just examining character arcs or plot points; it also requires an understanding of the cultural values embedded within the narrative. The primary objective of this study is to identify similarities and differences between the depiction of gender roles and cultural expectations in the film and those prevalent in Indonesian traditional culture, and to understand how they intersect or diverge. Using a descriptive qualitative method, this research applies Charles S. Peirce’s semiotic analysis to examine gender roles and cultural expectations in Mulan, while conducting library research to explore gender roles in Indonesian society. The study reveals that there are notable similarities between the two contexts, particularly regarding the roles of women as household keepers, their loyalty to family, and their submissiveness to patriarchal expectations. However, both narratives also reflect evolving challenges to these traditional norms. In conclusion, the study highlights the parallels between traditional gender expectations in Mulan and Indonesian culture, while acknowledging the gradual shift toward gender role redefinition in both societies. Keywords: gender, gender roles, cultural expectation